Pengaruh Perputaran Kas, Kecukupan Modal, dan Risiko Kredit Pada Profitabilitas LPD di Kabupaten Gianyar - Febriani, Sang Ayu Diah; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p20, 2019)
This study aims to determine the factors that affect the profitability of LPDs by using variable cash turnover, capital adequacy and credit risk. This study hypothesizes cash turnover, capital adequacy, and credit risk and LPD profitability. This research took place in the LPD of the Regency of Gianyar. The sampling method uses probability sampling with proportional stratified random sampling technique. The research data were sourced from LPD financial report data recorded in the Gianyar Regency LPLPD. Analysis of research data using multiple linear regression. The results showed that cash turnover and capital adequacy has a positive effect on LPD profitability in Gianyar Regency. But, credit risk has a negative effect on the profitability of LPDs in Gianyar Regency. Based on the results of the study it is expected that the LPD is able to maintain the level of cash turnover, capital adequacy, and the level of credit risk. Keywords : Profitability; Cash Turnover; Capital Adequacy; Credit Risk.